Interaction of the high energy deuterons with the graphite target in the plasma focus devices based on Lee model - Akel, M.; Alsheikh Salo, S.; Ismael, SH.; Saw, S. H.; Lee, S. (AIP Publishing, 2014)
Numerical experiments are systematically carried out using the Lee model code extended to compute the ion beams on various plasma focus devices operated with Deuterium gas. The deuteron beam properties of the plasma focus are studied for low and high energy plasma focus device. The energy spectral distribution for deuteron ions ejected from the pinch plasma is calculated and the ion numbers with energy around 1 MeV is then determined. The deuteron–graphite target interaction is studied for different conditions. The yield of the reaction 12 C(d,n) 13 N and the induced radioactivity for one and multi shots plasma focus devices in the graphite solid target is investigated. Our results present the optimized high energy repetitive plasma focus devices as an alternative to accelerators for the production of 13 N short lived radioisotopes. However, technical challenges await solutions on two fronts: (a) operation of plasma focus machines at high rep rates for a sufficient period of time (b) design of durable targets that can take the thermal load.